2016
DOI: 10.1007/s00595-016-1331-7
|View full text |Cite
|
Sign up to set email alerts
|

Open surgery versus laparoscopic surgery after stent insertion for obstructive colorectal cancer

Abstract: The patients who underwent laparoscopic resection had less blood loss, although no significant difference was found in postoperative morbidity or mortality. Thus, laparoscopic resection after stent insertion is a feasible and safe option for patients with obstructive colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Using a metallic stent for acute obstructive colorectal cancer has been well assessed and established as an effective procedure . SEMS were successfully inserted as a BTS in 97.1% of patients in our study.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Using a metallic stent for acute obstructive colorectal cancer has been well assessed and established as an effective procedure . SEMS were successfully inserted as a BTS in 97.1% of patients in our study.…”
Section: Discussionmentioning
confidence: 71%
“…Law et al reported that laparoscopic mobilization was not particularly difficult and the amount of blood loss was low . Several articles have reported that laparoscopic surgery after SEMS had short‐term outcomes that were better than or comparable to those of open surgery after SEM . We think that the stent‐laparoscopic procedure should be performed by skilled surgeons because the tumor size is larger than in non‐obstructive cancer, and edema or invasion around the tumor can make the procedure complicated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 1 shows our current therapeutic strategy for managing patients with obstructive colorectal cancers. The standard approach begins with colonic stenting, which is then followed by laparoscopic surgery independent of the location of the obstruction on the right or left side 29,30) .…”
Section: Transanal Drainage: Colonic Stent Versus Transanal Drainage mentioning
confidence: 99%
“…Several previous studies demonstrated the superiority of SEMS over emergency surgery in terms of short-term outcomes (8)(9)(10). The feasibility of laparoscopic surgery after SEMS placement was also reported by several investigators (11)(12)(13). However, studies comparing the efficacy of SEMS and decompression tubes as a BTS are limited (14,15), as are studies comparing the usefulness of SEMS and decompression tubes as a bridge to laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 87%